2023
DOI: 10.1002/pul2.12184
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pulmonary hypertension after successful tuberculosis treatment in a community sample of adult patients

Abstract: There are an estimated 155 million survivors of tuberculosis (TB). Clinical experience suggests that post tuberculosis lung disease (PTLD) is an important cause of Group 3 pulmonary hypertension (PH). However, TB is not listed as a cause of PH in most guidelines. A cross‐sectional, community‐based study was conducted in nonhealthcare seeking adults who had successfully completed TB treatment. Subjects underwent questionnaires, spirometry, a 6‐min walk distance test (6MWD) and transthoracic echocardiography (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Sensitivity analysis showed that removing studies with a higher risk of bias resulted in a lower overall prevalence whereas the removal of studies with smokers or HIV participants had little effect on the overall estimates (supplementary material, table S4). In four studies where PH was diagnosed by echocardiography, the mean PASP was reported, yielding a pooled mean PASP of 58.6 mmHg (95% CI 52.8-64.4) in these studies [18,[30][31][32].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity analysis showed that removing studies with a higher risk of bias resulted in a lower overall prevalence whereas the removal of studies with smokers or HIV participants had little effect on the overall estimates (supplementary material, table S4). In four studies where PH was diagnosed by echocardiography, the mean PASP was reported, yielding a pooled mean PASP of 58.6 mmHg (95% CI 52.8-64.4) in these studies [18,[30][31][32].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…LOUW et al [30] KALLA et al implications that may be related to TB-associated PH, appropriate targeted screening may indeed have long-term cost benefits [4,34].…”
Section: Hospitalised Patients and Symptomatic Outpatientsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Early data show no associations with spirometry, HIV and 6-minute walk distance, but a possible association with cigarette smoking and multiple episodes of TB. 20 The relationship between parenchymal damage and presence of PH is unclear, with univariate associations not maintaining significance after adjustment for confounders. 21 23 However, PH post-TB appears to have higher mortality and hospital readmission rates than PH in other chronic lung diseases.…”
Section: Cardiovascular and Pulmonary Vascular Disease Working Groupmentioning
confidence: 99%
“… 17 , 18 Prospective data show some recovery of lung function within the first year after TB treatment completion, but a high proportion of individuals experience ongoing symptoms or abnormal spirometry beyond this. 19 Long term respiratory consequences of residual lung pathology amongst TB survivors are heterogenous 8 , 10 , 11 and poorly described, but may include secondary bacterial infections, fungal colonisation and disease, 20 pulmonary hypertension, 21 and increased mortality rates for the minority with more severe lung damage. 22 It is possible that chronic respiratory disease may itself be a risk factor for PTB disease, and the high burden of residual respiratory pathology and impairment observed amongst TB survivors may in part reflect pre-existent, as well as TB-related, lung damage.…”
Section: Introductionmentioning
confidence: 99%